Astaxanthine attenuates cisplatin ototoxicity in vitro and protects against cisplatin-induced hearing loss in vivo - Benyu Nan; Zirui Zhao; Kanglun Jiang; Xi Gu; Huawei Li; Xinsheng Huang (Elsevier, 2022)
Astaxanthine (AST) has important biological activities including antioxidant and anti-inflammatory effects that could alleviate neurological and heart diseases, but its role in the prevention of cisplatin-induced hearing loss (CIHL) is not yet well understood. In our study, a steady interaction between AST and the E3 ligase adapter Kelch-like ECH-associated protein 1, a predominant repressor of nuclear factor erythroid 2-related factor 2 (NRF2), was performed and tested via computer molecular docking and dynamics. AST protected against cisplatin-induced ototoxicity via NRF2 mediated pathway using quantitative PCR and Western blotting. The levels of reactive oxygen species (ROS) and mitochondrial membrane potential revealed that AST reduced ROS overexpression and mitochondrial dysfunction. Moreover, AST exerted anti-apoptosis effects in mouse cochlear explants using immunofluorescence staining and HEI-OC1 cell lines using quantitative PCR and Western blotting. Finally, AST combined with poloxamer was injected into the middle ear through the tympanum, and the protection against CIHL was evaluated using the acoustic brain stem test and immunofluorescent staining in adult mice. Our results suggest that AST reduced ROS overexpression, mitochondrial dysfunction, and apoptosis via NRF2-mediated pathway in cisplatin-exposed HEI-OC1 cell lines and mouse cochlear explants, finally promoting cell survival. Our study demonstrates that AST is a candidate therapeutic agent for CIHL.